Agama dan Pembentukan Cara Pandang Serta Perilaku Hidup Masyarakat - Lakonawa, Petrus (Bina Nusantara University, 2013)
Religion is one of the most decisive factors in promoting the values and virtues of life in the community. Through religious teachings and practices, religion directs human’s perspective and the life of the community. In this article the author aims at discussing on how religions form their members’ worldview and perspective. The author will focus on the religious rituals, scriptures, and ethics. The purpose of this discussion is to raise the audience's awareness of the relevance of religion in human life and the importance of critical scrutiny of the content of religious teachings in order to promote common good for the whole creatures.